Preparation method of alpha-Fe2O3 multilayer nano hollow globulin stone array

By preparing α-Fe2O3 multi-layer nano hollow globulin arrays, the problem of reducing the film thickness is solved, and efficient photoelectric conversion and the effect of reducing production costs is achieved.

CN119683862APending Publication Date: 2025-03-25CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411966804.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, due to the decrease in the thickness of the α-Fe2O3 film, its absorption capacity to light will also be reduced accordingly, resulting in a decrease in the overall efficiency of the electrode.

Method used

A multi-layer nano-hollow globulin array preparation method was adopted to prepare an α-Fe2O3 multi-layer nano-hollow globulin array by pretreating the FTO conductive glass substrate, and then using impregnation vacuum evaporation self-assembly method, and the α-Fe2O3 multi-layer nano-hollow globulin array was obtained by immersion method and high-temperature annealing treatment.

Benefits of technology

It maintains a high light absorption capacity, reduces production costs, has good application prospects, and improves the overall efficiency of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683862A_ABST
    Figure CN119683862A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano material preparation, in particular to a preparation method of an alpha-Fe2O3 multilayer nano hollow globulin stone array, which comprises the following steps: firstly, pretreating an FTO (Fluorine-doped Tin Oxide) conductive glass substrate; then preparing a polystyrene microsphere template with a multi-layer opal structure on an FTO conductive glass substrate by adopting an impregnation vacuum evaporation self-assembly method; finally, based on the multi-layer opal structure polystyrene microsphere template, an impregnation method and high-temperature annealing treatment are adopted, and the alpha-Fe2O3 multi-layer nano hollow globulin array is obtained.The array structure prepared through the method has a multi-layer periodically-arranged nano hollow sphere structure, a functionalized nano shell layer and a sufficient internal space, and meanwhile, the nano hollow globulin array can be used for preparing a multi-layer nano hollow globulin array. The preparation method is simple, is low in cost, greatly reduces the production cost, has a good application prospect, and solves the technical problem in the prior art that the light absorption capability of the thin film is correspondingly weakened due to the reduction of the thickness of the thin film, so that the overall efficiency of the electrode is adversely affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation, in particular to an α-Fe 2 O 3 Preparation method of multilayer nano hollow spherical opal array. Background Art

[0002] As a typical structure of photonic crystals, functional films based on opal structures present typical periodic arrangements, which can produce colorful structural colors. Structural colors have advantages such as high saturation, high brightness, iridescence effect, polarization effect and never fading, which are not possessed by other chemical colors. At present, they are widely used in optoelectronic functional materials, display anti-counterfeiting materials, and biofunctional materials. Hollow nanostructures have great potential for advanced energy storage and conversion applications due to their functionalized nanoshells and ample internal space. In the past decade, a lot of research work has been devoted to the design and synthesis of hollow nanostructures with high complexity, and their electrochemical performance has been improved by manipulating their geometric morphology, chemical position, building blocks and internal structure to meet the growing global demand for renewable and sustainable energy.

[0003] Photoelectrochemical hydrogen production technology has shown great potential for efficiently converting solar energy into chemical energy. 2 O 3 As a semiconductor photoelectrode material, it has received extensive attention. Due to its suitable bandgap width (2.1eV), excellent chemical stability, environmental friendliness, low cost and easy availability, it is considered to be a new generation of solar water splitting hydrogen production semiconductor material with great research value and application prospects. However, the short photogenerated carrier lifetime (<10ps) and transmission distance (2-4nm) lead to low photogenerated electron-hole separation efficiency, making α-Fe 2 O 3 The actual solar hydrogen production efficiency is far lower than the theoretical value.

[0004] In the prior art, in order to shorten the hole collection distance and more effectively utilize the generated carriers, thinner α-Fe 2 O 3 However, as the thickness of the film decreases, its ability to absorb light will also decrease accordingly, which will have an adverse effect on the overall efficiency of the electrode. Summary of the invention

[0005] The present invention aims to provide an α-Fe 2 O 3The method for preparing a multilayer nano hollow spherical opal array is intended to solve the technical problem in the prior art that due to the reduction in film thickness, its light absorption capacity will be correspondingly weakened, which will have an adverse effect on the overall efficiency of the electrode.

[0006] In order to achieve the above object, the present invention adopts an α-Fe 2 O 3 The method for preparing a multilayer nano hollow spherical opal array comprises the following steps: Step 1: First, pretreat the FTO conductive glass substrate; Step 2: Subsequently, a multi-layer opal structure polystyrene microsphere template is prepared on the FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method; Step 3: Based on the multilayer opal structure polystyrene microsphere template, α-Fe 2 O 3 Multilayered nanohollow spherical opal arrays.

[0007] Among them, in step 1, the FTO conductive glass substrate is pretreated including cleaning and hydrophilic treatment, and the specific method is as follows: First, the FTO conductive glass substrate was ultrasonically treated in a cleaning solution and water for 5-20 min in sequence; Then blow dry with nitrogen; Then, the FTO conductive glass substrate is immersed in the hydrophilic solution and kept at 70-80° C. for 0.5-3 h, preferably at 75° C. for 1 h.

[0008] Wherein, the cleaning liquid is any one or more of isopropanol, acetone or ethanol; The hydrophilic solution is a mixed solution of ammonia water, hydrogen peroxide and water, and the volume ratio of ammonia water, hydrogen peroxide and water is 1:1:5. Meanwhile, other ratios are also applicable to the present invention as long as the FTO conductive glass substrate can obtain good hydrophilic properties.

[0009] Among them, in step 2, the specific method of preparing a multi-layer opal structure polystyrene microsphere template on a FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method is: Firstly, polystyrene beads are mixed with deionized water and evenly dispersed to obtain a polystyrene bead dispersion; Subsequently, the hydrophilic FTO conductive glass substrate was vertically suspended in a polystyrene colloidal sphere suspension and a densely packed multilayer opal structured polystyrene microsphere template was prepared under vacuum conditions at 50 °C.

[0010] Wherein, the diameter of the polystyrene sphere is 800nm.

[0011] When the polystyrene beads are mixed with deionized water and uniformly dispersed, the weight ratio of the polystyrene beads to the deionized water is 2:10. 3 .

[0012] When the polystyrene beads are mixed with deionized water and evenly dispersed, ultrasonic dispersion is used for dispersion.

[0013] Wherein, in step three, the annealing condition is annealing at 350°C for 2h in air with a heating rate of 10°C / min.

[0014] An α-Fe 2 O 3 The preparation method of multilayer nano hollow sphere opal array comprises the following steps: firstly, pretreating the FTO conductive glass substrate; then, preparing a multilayer opal structure polystyrene microsphere template on the FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method; finally, based on the multilayer opal structure polystyrene microsphere template, an immersion method and high temperature annealing treatment are used to obtain α-Fe 2 O 3 The multi-layer nano hollow sphere opal array has a multi-layer periodically arranged nano hollow sphere structure with a functionalized nano shell and sufficient internal space. At the same time, the preparation method is simple and low in cost, which greatly reduces the production cost and has good application prospects. In this way, the technical problem that the light absorption capacity of the film is weakened due to the reduction of the film thickness in the prior art is solved, which will have an adverse effect on the overall efficiency of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 3 is a SEM plan view of a multilayer polystyrene sphere film array having a diameter of 800 nm obtained in step S4 of Example 1 of the present invention.

[0017] Figure 2 It is a SEM cross-sectional view of a multilayer polystyrene sphere film array with a diameter of 800 nm obtained in step S4 of Example 1 of the present invention.

[0018] Figure 3 The α-Fe obtained in step S4 of Example 1 of the present invention 2 O 3 SEM plan view of multilayer nanohollow spherical opal array.

[0019] Figure 4 The α-Fe obtained in step S4 of Example 1 of the present invention 2 O 3 SEM cross-sectional image of multilayer nanohollow spherical opal array. DETAILED DESCRIPTION

[0020] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0021] The present invention provides an α-Fe 2 O 3 The method for preparing a multilayer nano hollow spherical opal array comprises the following steps: Step 1: First, pretreat the FTO conductive glass substrate; According to this specific embodiment, the FTO conductive glass substrate is pretreated including cleaning and hydrophilic treatment, and the specific method is as follows: First, the FTO conductive glass substrate was ultrasonically treated in a cleaning solution and water for 5-20 min in sequence; Then blow dry with nitrogen; Then, the FTO conductive glass substrate is immersed in the hydrophilic solution and kept at 70-80° C. for 0.5-3 h, preferably at 75° C. for 1 h.

[0022] The cleaning liquid is any one or more of isopropanol, acetone or ethanol; The hydrophilic solution is a mixed solution of ammonia water, hydrogen peroxide and water, and the volume ratio of ammonia water, hydrogen peroxide and water is 1:1:5. Meanwhile, other ratios are also applicable to the present invention as long as the FTO conductive glass substrate can obtain good hydrophilic properties.

[0023] Step 2: Subsequently, a multi-layer opal structure polystyrene microsphere template is prepared on the FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method; For this specific implementation, The specific method of preparing a multi-layer opal structure polystyrene microsphere template on a FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method is as follows: Firstly, polystyrene beads are mixed with deionized water and evenly dispersed to obtain a polystyrene bead dispersion; Subsequently, the hydrophilic FTO conductive glass substrate was vertically suspended in a polystyrene colloidal sphere suspension and a densely packed multilayer opal structured polystyrene microsphere template was prepared under vacuum conditions at 50 °C.

[0024] The diameter of the polystyrene beads is 800 nm.

[0025] When the polystyrene beads are mixed with deionized water and uniformly dispersed, the weight ratio of the polystyrene beads to the deionized water is 2:10. 3 .

[0026] When the polystyrene beads are mixed with deionized water and dispersed uniformly, ultrasonic dispersion is used for dispersion.

[0027] Step 3: Based on the multilayer opal structure polystyrene microsphere template, α-Fe 2 O 3 Multilayered nanohollow spherical opal arrays.

[0028] For this specific implementation, the annealing condition is annealing at 350° C. for 2 h in air with a heating rate of 10° C. / min. See also Figures 1 to 4 , Figure 1 3 is a SEM plan view of a multilayer polystyrene sphere film array having a diameter of 800 nm obtained in step S4 of Example 1 of the present invention. Figure 2 It is a SEM cross-sectional view of a multilayer polystyrene sphere film array with a diameter of 800 nm obtained in step S4 of Example 1 of the present invention. Figure 3 The α-Fe obtained in step S4 of Example 1 of the present invention 2 O 3 SEM plan view of multilayer nanohollow spherical opal array. Figure 4 The α-Fe obtained in step S4 of Example 1 of the present invention 2 O 3 SEM cross-sectional image of multilayer nanohollow spherical opal array. Example

[0029] In this embodiment, α-Fe 2 O 3 The process of preparing multilayer nano hollow spherical opal array is as follows: S1. First, the FTO conductive glass substrate was cleaned in ethanol, acetone and deionized water for 5 min in sequence by ultrasonic cleaning, and then dried with nitrogen; S2, immersing the blow-dried FTO conductive glass substrate in a mixed solution of ammonia water, hydrogen peroxide and water in a volume ratio of 1:1:5 at 75°C for 1 hour for hydrophilic treatment, pouring out the liquid after cooling, rinsing with deionized water and blowing dry with nitrogen; S3, then the polystyrene beads with a diameter of 800nm ​​and deionized water were mixed in a weight ratio of 2:10 3 Mixing and ultrasonically dispersing to obtain a polystyrene ball dispersion; S4, vertically suspending the hydrophilic treated FTO conductive glass substrate in a polystyrene ball dispersion, and preserving it at 50° C. under vacuum conditions for 24 h to prepare a densely packed multilayer opal structure polystyrene microsphere template for later use; S5. The obtained multilayer opal structure polystyrene microsphere template was soaked in methanol solution and then quickly taken out, and then immersed in FeCl 3 •6H 2 O aqueous solution, then naturally air-dried at room temperature, and finally annealed at 350 ° C for 2 hours in air at a heating rate of 10 ° C / min to obtain α-Fe 2 O 3 Multilayered nanohollow spherical opal arrays. Example

[0030] In this embodiment, α-Fe 2 O 3 The process of preparing multilayer nano hollow spherical opal array is as follows: S1. First, the FTO conductive glass substrate was cleaned in ethanol, acetone and deionized water for 5 min in sequence by ultrasonic cleaning, and then dried with nitrogen; S2, immersing the blow-dried FTO conductive glass substrate in a mixed solution of ammonia water, hydrogen peroxide and water in a volume ratio of 1:1:5 at 75°C for 1 hour for hydrophilic treatment, pouring out the liquid after cooling, rinsing with deionized water and blowing dry with nitrogen; S3, then polystyrene beads with a diameter of 400nm and deionized water were mixed in a weight ratio of 2:10 3 Mixing and ultrasonically dispersing to obtain a polystyrene ball dispersion; S4, vertically suspending the hydrophilic treated FTO conductive glass substrate in a polystyrene ball dispersion, and preserving it at 50° C. under vacuum conditions for 24 h to prepare a densely packed multilayer opal structure polystyrene microsphere template for later use; S5. The obtained multilayer opal structure polystyrene microsphere template was soaked in methanol solution and then quickly taken out, and then immersed in FeCl 3 •6H 2 O aqueous solution, then naturally air-dried at room temperature, and finally annealed at 350 ° C for 2 hours in air at a heating rate of 10 ° C / min to obtain α-Fe 2 O 3 Multilayered nanohollow spherical opal arrays. Example

[0031] In this embodiment, α-Fe 2 O 3 The process of preparing multilayer nano hollow spherical opal array is as follows: S1. First, the FTO conductive glass substrate was cleaned in ethanol, acetone and deionized water for 5 min in sequence by ultrasonic cleaning, and then dried with nitrogen; S2, immersing the blow-dried FTO conductive glass substrate in a mixed solution of ammonia water, hydrogen peroxide and water in a volume ratio of 1:1:5 at 75°C for 1 hour for hydrophilic treatment, pouring out the liquid after cooling, rinsing with deionized water and blowing dry with nitrogen; S3, then the polystyrene beads with a diameter of 800nm ​​and deionized water were mixed in a weight ratio of 5:10 3 Mixing and ultrasonically dispersing to obtain a polystyrene ball dispersion; S4, vertically suspending the hydrophilic treated FTO conductive glass substrate in a polystyrene ball dispersion, and preserving it at 50° C. under vacuum conditions for 24 h to prepare a densely packed multilayer opal structure polystyrene microsphere template for later use; S5. The obtained multilayer opal structure polystyrene microsphere template was soaked in methanol solution and then quickly taken out, and then immersed in FeCl 3 •6H 2 O aqueous solution, then naturally air-dried at room temperature, and finally annealed at 350 ° C for 2 hours in air at a heating rate of 10 ° C / min to obtain α-Fe 2 O 3 Multilayered nanohollow spherical opal arrays. Example

[0032] In this embodiment, α-Fe 2 O 3 The process of preparing multilayer nano hollow spherical opal array is as follows: S1. First, the FTO conductive glass substrate was cleaned in ethanol, acetone and deionized water for 5 min in sequence by ultrasonic cleaning, and then dried with nitrogen; S2, immersing the blow-dried FTO conductive glass substrate in a mixed solution of ammonia water, hydrogen peroxide and water in a volume ratio of 1:1:5 at 75°C for 1 hour for hydrophilic treatment, pouring out the liquid after cooling, rinsing with deionized water and blowing dry with nitrogen; S3, then the polystyrene beads with a diameter of 800nm ​​and deionized water were mixed in a weight ratio of 2:10 3 Mixing and ultrasonically dispersing to obtain a polystyrene ball dispersion; S4, vertically suspending the hydrophilic treated FTO conductive glass substrate in a polystyrene ball dispersion, and preserving it at 50° C. under vacuum conditions for 24 h to prepare a densely packed multilayer opal structure polystyrene microsphere template for later use; S5. The obtained multilayer opal structure polystyrene microsphere template was soaked in methanol solution and then quickly taken out, and then immersed in FeCl3 •6H 2 O aqueous solution, then naturally air-dried at room temperature, and finally annealed at 350 ° C for 2 hours in air at a heating rate of 10 ° C / min to obtain α-Fe 2 O 3 Multilayered nanohollow spherical opal arrays.

[0033] Using the α-Fe 2 O 3 The method for preparing a multilayer nano hollow spherical opal array comprises the following steps: firstly, pretreating an FTO conductive glass substrate; then, using an immersion vacuum evaporation self-assembly method to prepare a multilayer opal structure polystyrene microsphere template on the FTO conductive glass substrate; finally, based on the multilayer opal structure polystyrene microsphere template, using an immersion method and high temperature annealing treatment to obtain an α-Fe 2 O 3 The multi-layer nano hollow sphere opal array has a multi-layer periodically arranged nano hollow sphere structure with a functionalized nano shell and sufficient internal space. At the same time, the preparation method is simple and low in cost, which greatly reduces the production cost and has good application prospects. In this way, the technical problem that the light absorption capacity of the film is weakened due to the reduction of the film thickness in the prior art is solved, which will have an adverse effect on the overall efficiency of the electrode.

[0034] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing an α-Fe2O3 multilayer nano hollow spherical opal array, characterized in that: The steps include: Step 1: First, pretreat the FTO conductive glass substrate; Step 2: Subsequently, a multi-layer opal structure polystyrene microsphere template is prepared on the FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method; Step 3: Based on the multilayer opal structure polystyrene microsphere template, an α-Fe2O3 multilayer nano hollow sphere opal array is obtained by using an impregnation method and high temperature annealing treatment.

2. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 1, characterized in that: In step 1, the FTO conductive glass substrate is pre-treated including cleaning and hydrophilic treatment, and the specific method is as follows: First, the FTO conductive glass substrate was ultrasonically treated in a cleaning solution and water for 5-20 min in sequence; Then blow dry with nitrogen; Then, the FTO conductive glass substrate is immersed in the hydrophilic solution and kept at 70-80° C. for 0.5-3 h, preferably at 75° C. for 1 h.

3. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 2, characterized in that: The cleaning liquid is any one or more of isopropanol, acetone or ethanol; The hydrophilic solution is a mixed solution of ammonia water, hydrogen peroxide and water, and the volume ratio of ammonia water, hydrogen peroxide and water is 1:1:

5.

4. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 3, characterized in that: In step 2, the specific method of preparing a multi-layer opal structure polystyrene microsphere template on a FTO conductive glass substrate by using an immersion vacuum evaporation self-assembly method is as follows: Firstly, polystyrene beads are mixed with deionized water and evenly dispersed to obtain a polystyrene bead dispersion; Subsequently, the hydrophilic FTO conductive glass substrate was vertically suspended in a polystyrene colloidal sphere suspension and a densely packed multilayer opal structured polystyrene microsphere template was prepared under vacuum conditions at 50 °C.

5. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 4, characterized in that: The diameter of the polystyrene beads is 800 nm.

6. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 5, characterized in that: When the polystyrene beads are mixed with deionized water and uniformly dispersed, the weight ratio of the polystyrene beads to the deionized water is 2:

10. 3 .

7. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 6, characterized in that: When the polystyrene beads are mixed with deionized water and dispersed uniformly, ultrasonic dispersion is used for dispersion.

8. The method for preparing the α-Fe2O3 multilayer nano hollow spherical opal array according to claim 7, characterized in that: In step three, the annealing condition is 350°C annealing for 2h in air with a heating rate of 10°C / min.